(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article the author reveals the new institute criminal proceedings as an investigative judge. The author also reveals the features of the authorization of detention by the investigating judge at the pre-trial investigation stage. The author points out of seven bases, the presence of which may be authorized by a measure of restraint in the form of detention against the person who committed the crime. Disclose the procedure for applying preventive measures. It displays the features of the application of detention. Key words: the investigating judge, the criminal proceedings, the subject of criminal proceedings, a sanction.